Utilization of Technology in Education: Increasing Learning Interactivity - Eka Nurmala; Diah Vitaloka Hartati; Baihaqi Baihaqi (PT. Alpha Trianguli Australis, 2025)
The rapid development of information and communication technology has brought significant changes to the educational landscape, particularly in enhancing learning interactivity. Interactivity is a critical component of the learning process, as it directly contributes to student engagement, motivation, and understanding. This article aims to examine the utilization of technology in education and its role in improving learning interactivity through a literature review approach. The research method employed is a systematic literature study analyzing various scholarly sources, including textbooks, national and international journal articles, and relevant research reports related to educational technology and interactive learning. The analysis was conducted to identify key patterns, dominant approaches, and the impacts of technology integration on the learning process. The findings indicate that the use of educational technology, such as learning management systems, interactive multimedia, online learning platforms, and blended learning models, significantly enhances interactions between teachers and students, among students, and between students and learning materials. Technology also supports the creation of flexible, collaborative, and student-centered learning environments. However, the effectiveness of technology utilization is strongly influenced by teachers’ digital competencies, the availability of supporting infrastructure, and students’ ability to use technology effectively. Therefore, the integration of technology in education should be implemented in a well-planned and sustainable manner, accompanied by continuous professional development for educators and institutional policy support. This article concludes that technology should not be viewed merely as an instructional tool, but as a strategic medium for enhancing learning interactivity and improving overall educational quality.